Molecular architecture and assembly of the DDB1–CUL4A ubiquitin ligase machinery - Angers, Stephane; Li, Ti; Yi, Xianhua; MacCoss, Michael J.; Moon, Randall T.; Zheng, Ning (Nature, 2006)
Protein ubiquitination is a common form of post-translational modification that regulates a broad spectrum of protein substrates in diverse cellular pathways 1 . Through a three-enzyme (E1–E2–E3) cascade, the attachment of ubiquitin to proteins is catalysed by the E3 ubiquitin ligase, which is best represented by the superfamily of the cullin-RING complexes 2 , 3 . Conserved from yeast to human, the DDB1–CUL4–ROC1 complex is a recently identified cullin-RING ubiquitin ligase, which regulates DNA repair 4 , 5 , 6 , 7 , 8 , 9 , 10 , DNA replication 11 , 12 , 13 , 14 and transcription 15 , and can also be subverted by pathogenic viruses to benefit viral infection 16 . Lacking a canonical SKP1-like cullin adaptor and a defined substrate recruitment module, how the DDB1–CUL4–ROC1 E3 apparatus is assembled for ubiquitinating various substrates remains unclear. Here we present crystallographic analyses of the virally hijacked form of the human DDB1–CUL4A–ROC1 machinery, which show that DDB1 uses one β-propeller domain for cullin scaffold binding and a variably attached separate double-β-propeller fold for substrate presentation. Through tandem-affinity purification of human DDB1 and CUL4A complexes followed by mass spectrometry analysis, we then identify a novel family of WD40-repeat proteins, which directly bind to the double-propeller fold of DDB1 and serve as the substrate-recruiting module of the E3. Together, our structural and proteomic results reveal the structural mechanisms and molecular logic underlying the assembly and versatility of a new family of cullin-RING E3 complexes.